Helping Amid the Pandemic: Daily Affective and Social Implications of COVID-19-Related Prosocial Activities. (13th October 2020) - Sin, Nancy L; Klaiber, Patrick; Wen, Jin H; DeLongis, Anita
Abstract: Background and Objectives: The novel coronavirus disease 2019 (COVID-19) pandemic may have prompted more engagement in prosocial activities, such as volunteering and support transactions. The day-to-day affective and social implications of these activities for adults of different ages are unknown. The current study examined associations of daily prosocial activities with affective and social well-being, and whether these associations varied by age. Research Design and Methods: Participants ages 18–91 in Canada and the United States ( N = 1, 028) completed surveys for 7 consecutive evenings about their daily experiences of COVID-19-related prosocial activities (formal volunteering, support provision, support receipt), positive and negative affect, and satisfaction with social activities and relationships. Analyses were conducted using multilevel modeling and accounted for a range of potential confounding factors (e.g., sociodemographics, work, family, caregiving, daily stressors). Results: Older age predicted more frequent formal volunteering, as well as more support provision and support receipt due to COVID-19. In particular, middle-aged and older adults provided more emotional support than younger adults, middle-aged adults provided the most tangible support, and older adults received the most emotional support. All three types of prosocial activities were associated with higher positive affect and greater social satisfaction on days when they occurred. Providing COVID-19-related support further predicted lower same-day negative affect. Age did not significantly moderate these associations. Discussion and Implications: Older age was related to more frequent engagement in prosocial activities during the COVID-19 crisis. These activities were associated with improved daily affective and social well-being for adults of all ages.